Intrinsic Motivation Mediates the Association Between Exercise-Associated Affect and Physical Activity Among Adolescents - Schneider, Margaret (Frontiers in Psychology, 2018)
American adolescents overwhelmingly engage in insufficient physical activity (PA). Attention has turned to the role of affect in shaping PA, raising questions as to whether the impact of affect on PA is direct/automatic or cognitively mediated (“Type 1” or “Type 2” in the dual-process model). This study examines whether intrinsic motivation (IM) mediates the association between affect and PA. Adolescents (N = 142, 48% Male, 20% non-Latino White, mean age = 11.04 years, mean VO2 = 37.19 ml/kg/min, mean BMI = 63.19) completed assessments of cardiorespiratory fitness, affective response to exercise on a stationary cycle, IM, preferred exercise intensity, and moderate-to-vigorous PA (MVPA; ActiGraph). Fitness, exercise intensity and MVPA assessments were repeated 5 months later. Tests for mediation showed that affect predicted PA at baseline and 5 months, and IM mediated the relationship between affect and PA both cross-sectionally (CI = 0.03, 0.17) and longitudinally (CI = 0.04, 0.18). Results suggest a cognitively mediated pathway from affect to behavior. Adolescent PA may be increased either by enhancing IM or by tailoring interventions to accommodate individuals with a predisposition to respond to exercise with negative affect. This study is registered with Clinicaltrials.gov (ID # NCT01876602).